Мастер взрывного дела: Роман / А. А. Ильин - Ильин Андрей Александрович (ЭКСМО, 2002)
Экземпляры: РБ (20160309) / Инвентарный номер: 35541 / Цена: 52.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: И 46 / ББК: 84(2Рос=Рус)6